Clockwork angel - Clare, Cassandra (New York Margaret K. McElderry Books, 2011)
When sixteen-year-old orphan Tessa gray's older brother suddenly vanishes, her search for him leads her into Victorian-era London's dangerous supernatural underworld, and when she discovers that she herself is a Downworlder, she must learn to trust the demon-killing Shadowhunters if she ever wants to learn to control her powers and find her brother
"Bonus content inside! The original story "Magnus's vow"--Cover
Ages 14 up
1
NEW, LITERATURE
Keywords: Demonology -- Fiction; London (England) -- History -- 19th century -- Fiction; Orphans -- Fiction; Secret societies -- Fiction; Supernatural -- Fiction; Great Britain -- History -- Victoria, 1837-1901 -- Fiction